Self Efficacy and Academic Anxiety as Predictors of Cheating Behavior among Madrasah Aliyah Students - Amelia Nur Chumairoh; Annas Ribab Sibilana (Journal of Education and Learning Sciences, 2026)
Education in Indonesia still faces various challenges, one of which is cheating behavior that reflects low levels of students’ academic integrity. In the learning of Islamic Cultural History (SKI), this behavior frequently occurs because the material is perceived as difficult and less engaging. In addition, low self-efficacy leads to a lack of students’ confidence in completing tasks, while high academic anxiety encourages the emergence of cheating behavior as an instant solution. The purpose of this study is to address the following questions: (1) whether self-efficacy affects cheating behavior, (2) whether academic anxiety affects cheating behavior, and (3) to what extent both variables simultaneously influence cheating behavior. This study employs a quantitative approach with a correlational design, using questionnaires as the data collection technique and linear regression analysis (both partial and simultaneous) for data analysis. The research subjects are eleventh-grade students at MAN 2 Blitar. The results indicate that self-efficacy has a negative and significant effect on cheating behavior, while academic anxiety has a positive and significant effect. Simultaneously, both variables contribute 59% to cheating behavior. It is concluded that strengthening self-efficacy and managing academic anxiety are important in reducing students’ cheating behavior.